THE IMPORTANCE OF PHYSICAL ACTIVITY IN THE PREVENTION OF FATTY HEPATOSIS AND CHRONIC LIVER DISEASES - Zakirkhodjaev Sh. Y.; Jalolov N. N.; Soliyeva I. A. (American Journals Publishing, 2025)
This article provides a systematic overview of the role of physical activity or exercise therapy in the prevention of fatty hepatosis and chronic liver diseases. Various clinical studies, epidemiological observations and trials are analyzed to evaluate the effects of physical activity on reducing hepatic steatosis, improving serum enzyme levels, preventing fibrosis progression, and modifying liver-related risk factors. The clinical efficiency of exercise type, intensity and duration is also assessed. The findings indicate that physical activity can serve as a preventive strategy due to its influence on inflammation, insulin sensitivity, lipid metabolism, and other related mechanisms.
Keywords: fatty hepatosis, hepatitis, prevention, physical activity, exercise therapy, insulin sensitivity, inflammation.